PCT165 : Digital imaging techniques / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2025)
This course emphasizes the aesthetic, technical, and conceptual practices of image making using variety of process and methods in hardware and software application relate in digital technology. Students will be challenged to develop their own visual language and to create unique aesthetic and conceptual experiences to producing an image. This class will consist of lectures, software demonstrations, and image making exercises, projects, and readings. Students are evaluated based on their contribution to class discussions and critiques in regards to their digital image making practices.